Acquired Haemophilia A in the Elderly: Case Reports. (11th February 2010) - Tufano, Antonella; Coppola, Antonio; Guida, Anna; Cimino, Ernesto; De Gregorio, Angela Maria; Cerbone, Anna Maria; Di Minno, Giovanni
Abstract : Acquired hemophilia A (AHA) is a very rare disease, caused by the development of autoantibodies, directed against circulating factor VIII of coagulation. Age distribution is bimodal, with a first peak occurring among young women in the postpartum period, and a second major peak of incidence among elderly patients in whom it is frequently associated with malignancy and drugs. This disease often represents a life-threatening bleeding condition, especially in the elderly, thus requiring a prompt therapeutic intervention, including control of acute bleeding and eradication of the inhibitor by immunosuppressive therapy. The diagnosis of AHA should be considered in any elderly patient who presents with bleeding and prolonged activated Partial Thromboplastin Time. Moreover, the coexistence of a series of underlying diseases associated with AHA should be always searched for. An early recognition and an adequate treatment of this coagulation disorder and of the possible associated diseases play a significant role for a favourable outcome, but concomitant morbidities in the elderly may limit aggressive therapy and may complicate the clinical scenario. We report 3 consecutive elderly patients successfully treated with recombinant activated factor VII and standard immunosuppressive regimens, with remission of the disease.